A Pan Photoaffinity Probe for Detecting Active Forms of Matrix Metalloproteinases. Issue 1 (30th November 2012) - Nury, Catherine; Czarny, Bertrand; Cassar‐Lajeunesse, Evelyne; Georgiadis, Dimitris; Bregant, Sarah; Dive, Vincent
Abstract A photoaffinity probe based on the scaffold of a potent broad‐spectrum phosphinic peptide inhibitor of matrix metalloproteinases (MMPs) has been developed. A photolabile diazirine group for covalent modification of MMP active forms was incorporated at the P1′ position, and a tritium radioactive label for the sensitive detection of MMP covalent adducts by radioimaging was attached. The probe was characterized on seven catalytic domains of human MMPs (MMP‐2, ‐3, ‐8, ‐9, ‐12, ‐13 and ‐14) and was found to display nanomolar affinities towards this set of MMPs, covalently modifying them with crosslinking yields varying from 12 to 58 %, thus leading to highly sensitive detection of these MMPs. In a complex proteome complemented with four recombinant MMPs (MMP‐2, ‐9, ‐12 and ‐13), this probe enabled their simultaneous detection with a threshold of few femtomoles and low background labelling. Those properties should make this new pan‐activity‐based MMP probe a valuable tool for the detection of MMP active forms from biological fluids or tissue extracts.